1992
DOI: 10.1084/jem.176.5.1319
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 protects chronic lymphocytic leukemic B cells from death by apoptosis and upregulates Bcl-2 expression.

Abstract: SummaryB chronic lymphocytic leukemia (B-CLL) is characterized by the accumulation of slow-dividing and long-lived monoclonal B cells arrested at the intermediate stage of their differentiation . We previously showed that interleukin 4 (IL4) not only inhibits but also prevents the proliferation of B-CLL cells. We report here that IL-4 protects the B-CLL cells from death by apoptosis (programmed cell death [PCD]) . IL-4 inhibits spontaneous and hydrocortisone (HC)-induced PCD of highly purified B cells from 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
2
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(204 citation statements)
references
References 30 publications
7
190
2
4
Order By: Relevance
“…In keeping with previous studies, we found that the addition of recombinant IL-4 prevented the anti-IgM-induced growth arrest and apoptosis ( Figure 1). It has been shown that IL-4 can slow the proliferation of several tumor cell lines, a point confirmed in Figure 1A for CH31 cells [8,9,29]. Importantly, we observed that IL-4 reversed the potent growth inhibition caused by anti-IgM treatment ( Figure 1).…”
Section: Effect Of Il-4 On Anti-igm-induced Growth Arrest and Apoptosissupporting
confidence: 82%
See 1 more Smart Citation
“…In keeping with previous studies, we found that the addition of recombinant IL-4 prevented the anti-IgM-induced growth arrest and apoptosis ( Figure 1). It has been shown that IL-4 can slow the proliferation of several tumor cell lines, a point confirmed in Figure 1A for CH31 cells [8,9,29]. Importantly, we observed that IL-4 reversed the potent growth inhibition caused by anti-IgM treatment ( Figure 1).…”
Section: Effect Of Il-4 On Anti-igm-induced Growth Arrest and Apoptosissupporting
confidence: 82%
“…These effects are not limited to normal cells. In fact, IL-4 can regulate the survival of B-cell chronic lymphocytic leukemia (B-CLL, [8,9]). In this context, it is not surprising that a unique molecular signature of B-cell small lymphocytic lymphoma (SLL) is the elevated expression of the IL-4 receptor alpha chain [10].…”
Section: Introductionmentioning
confidence: 99%
“…3). Our results also suggest that the ability of IL-4 to promote proliferation as a cofactor is not solely attributed to the up-regulation of antiapoptotic genes, such as Bcl-2, by IL-4 stimulation (35), but it may be due to the synergistic induction of many genes involved in cell proliferation (Fig. 4).…”
Section: Gene Expression Change Patterns Distinguishing Il-4mentioning
confidence: 50%
“…According to the immunosurveillance theory, tumor initiation and progression are accompanied by the attack from host immune system (54) With these observations in normal B/T cells, it is easy to imagine that IL-4 promotes the survival of B/T cell-derived tumors. As early as in 1992, Danceca reported that IL-4 inhibited spontaneous and hydrocortisone-induced cell death of malignant B cells purified from patients with B chronic lymphocytic leukemia (67).…”
Section: Tumor Cells Express Elevated Amount Of Il-4rmentioning
confidence: 99%